Impact of Tree Species Mixture on Microbial Diversity and Community Structure in Soil Aggregates of Castanopsis hystrix Plantations - Rongao Zhang; Yijun Liu; Fei Cheng (Microorganisms)
Soil aggregates play a crucial role in maintaining the health and stability of artificial forest soil ecosystems, and microorganisms contribute to the formation and maintenance of soil aggregates. However, the impact of different tree species in mixed forests on soil aggregate microbial communities remains unclear. In this study, high-throughput sequencing technology was employed to analyze the bacterial and fungal diversity and community composition of four soil aggregate sizes (<0.25 mm, 0.25–1 mm, 1–2 mm, and >2 mm) in pure Castanopsis hystrix plantations (CK), mixed C. hystrix and Acacia crassicarpa plantations (MCA), mixed C. hystrix and Pinus massoniana plantations (MCP), and mixed C. hystrix and Mytilaria laosensis plantations (MCM). The results indicate that (1) establishing mixed forests enhances the diversity of bacterial and fungal communities in soil aggregates, and that soil aggregates with size <0.25 mm support higher microbial diversity. (2) The fungal and bacterial composition of soil aggregates in mixed forests differs from that of pure C. hystrix forests. The dominant bacterial phyla in the four forest types are Proteobacteria, Acidobacteria, Actinobacteria, and Chloroflexi. The dominant fungal phyla are Basidiomycota, Ascomycota, Mortierellomycota, and Mucoromycota. (3) PCoA analysis reveals that compared to pure C. hystrix forests, mixing with A. crassicarpa (MCA) results in marked changes in the bacterial community structure of soil aggregates; similarly, mixing with A. crassicarpa (MCA) and M. laosensis (MCM) leads to significant differences in the fungal community structure of soil aggregates. (4) RDA results show that NH4+-N, pH, and OC are the main factors influencing microbial diversity in soil aggregates. In terms of dominant microorganisms, pH and AP are the key environmental factors affecting the structure of bacterial and fungal communities in soil aggregates. The findings of this study contribute to our understanding of the characteristics of microbial communities in soil aggregates affected by tree mixing and provide a scientific reference for the maintenance and enhancement of soil fertility in planted forests.